Collaborative Pedagogy in a Design Thinking Education Course - Rosetta Marantz Cohen; Lucy Mule (Park University, 2019)
This article describes a co-taught course that mobilized a Design Thinking approach in the service of creating a prototype for an actual girls' boarding school in Kenya. The goal of the class was to allow students to engage collaboratively with faculty, with their peers, and with experts "on the ground" to develop the various parts of the school, from the mission to the curriculum to the building design. The article describes the rewards and complexities of this kind of hands-on pedagogy in a higher education context.